Improving the Management of Secondary and Tertiary Roads in the South East Europe Countries - World Bank (Washington, DC, 2012)
The importance of the tertiary road sector in contributing to economic development and poverty alleviation efforts cannot be understated. In Albania, forty-nine percent of rural producers have stated that a lack of adequate transportation, primarily good roads, was their biggest marketing problem. In Bosnia and Herzegovina, there is discontent about the quality of the regional and tertiary roads, with complaints about the low quality of roads foremost amongst all public services. In Former Yugoslav Republic (FYR) Macedonia, a recent survey has revealed tertiary roads to rank among the top three capital investment priorities in two-thirds of surveyed municipalities twelve percent listing as first priority, twenty-three percent as second priority and thirty-one percent as the third priority. Other studies have supported these findings but also report positive differences in school enrolment, and frequency in use of health services, between areas with and without all-weather roads. The best model of financing for tertiary (rural) roads is highly dependent on a particular country. The key to setting a policy framework for managing road networks is the realization that with constrained funding and specified target standards, there will be a finite limit to the size of the road network that can be maintained. By setting target standards and budget limits, road authorities effectively define the extent of road networks that can be maintained on a sustainable basis. Efforts should be made to increase options for local governments' own revenue sourcing and increase support from the central government in financing of maintenance operations.